Development of English Vocabulary Learning by Using Game for Grade 2 students - ยางเงิน, ชฎาพร (Chophayom Journal, 2019)
The objective of this research were 1) To study the development of learning English vocabulary using games for students in grade 2. 2) Development activities for learning English vocabulary using games for students in Grade 2, effective 80/80. 3) To compare the achievement of students before and after learning English, learning English vocabulary using games. 4) Study the student satisfaction toward the event of students in Grade 2. The target used in this research is students in grade 2 Phakumarnsuksa School, Phayakkhaphum Phisai district, MahaSarakham Province, 20 people by purposive Sampling. The finding of the Research found that 1) development activities to learn vocabulary in English through the game. for students in grade 2, there were 10 plans including 1.1) Introduce myself 1.2) My family 1.3) My Pet 1.4) Conversation at schools 1.5) Things in my school, 1.6) Food and drink 1.7) Repeat to Introduce myself 1.8) Parts of body 1.9) My favorite color 1.10) Number 2) Lesson plans develop activities for learning English vocabulary using games for students in Grade 2, Including performance management plan, learn English vocabulary using games for students in grade 2 is equal to 83.89 / 82.46.The higher than Efficiency criteria defined. 3) Learning achievement of students learning English vocabulary using games. After learning higher than that before learning at the 0.05 level of significance. 4) The satisfaction of students in Grade 2 at the event to learn English vocabulary using games. Overall the high level ( = 4.13) Keywords : Development Activities, English Vocabulary Learning